Sustainability: a comprehensive literature - Mukherjee, Aroop; Kamarulzaman, Nitty Hirawaty; Vijayan, Gowri; Vaiappuri, Selvakkumar K. N. (IGI Global, 2016)
Sustainability has become vital aspects for today's world and the future to come. Various definition of sustainability have added to the confusion with respect to sustainability in people's mind and in the organizations. A collection of different sustainability frameworks, indicators and tools have provided important insights about the outcomes of the sustainability process and in providing analytical and logical designs for sustainability. However, implementing sustainable practices has been overlooked by the majority of the organizations. Identifying the challenges and integrating with the tools in the form of indicators, assessment, and strategies will be a good start for an organization to be sustainable. The organizations that develop and implement sustainable practices are recognized as a success in sustainability. This chapter aims to provide an outline for sustainability with strategies, assessment, indicators, and application for better products and create and maintain business and customer value.